Fabrication of Metal Frame Partial Dentures with Alter Cast Technique - Syamsuddin, Rezki Wahyuni; Thalib, Bahruddin; Sutiyo, Sutiyo; Ikbal, Muhammad (Indonesian Journal of Prosthodontic, 2021)
Patient chief complaint: A female aged 48 years came to the Hasanuddin University Dental Hospital, Makassar. She complains difficulty of chewing and a lack of confidence. Patient status: Full edentulous maxillary and edentulous partial mandible. Diagnosis full edentulous maxillary and class 1 Kennedy mandible. Treatment plan: Fabrication of partial metal frame dentures using the altered case impression technique. Detail of therapy: Panoramic Radiological images appear to be missing all teeth in the maxilla, available teeth: 33,32, 31, 41, 42, and 43, residual the roots of teeth 15 and 28. The pre-prosthetic treatment plan was scaling and extracting the remaining roots on teeth 15 and 28. The first prosthodontic treatment is Preliminary impression was made. Subsequently, the diagnostic model is placed on top of the surveyor for inspection and design of the metal frame. Making individual impression upper and lower jaw using self-curing acrylic material, then doing border molding with greenstick. An additional laboratory procedure for altered cast technique is done by splitting the master cast with a saw. A groove or indentation is made on the cut surface of the mold to help retain the cast to be mixed. The denture metal frame is placed over the grooved mold. The final impression was then beading, and boxing made before it was cast with a cast so that an altered cast was obtained. Making bite rims of the maxilla and mandible and determining the alignment, vertical dimensions, using a bite rim made from the final impression, face-bow transfer, and installation on the articulator. Try the arrangement of teeth. Acrylic processing, selective remounting, and grinding. Denture inserted and controlled, checked for occlusion, articulation, retention, and stability. Clinical significance of therapy: Metal frame partial denture with Alter cast impression technique provides better and stable denture.